Musgos del Parque Nacional Los Marmoles, Hidalgo, Mexico - Delgadillo Moya, C.=700 1 Cardenas Soriano, M. de los A.; Galvez Aguilar, V.M.; Sanchez Gonzalez, A.
(Es, En)
Ilus., 18 ref.
Keywords: RESERVAS NATURALES; PARQUES NACIONALES; COMPOSICION BOTANICA; BRYOPHYTA; MEXICO; MUSGOS; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO